Chronic active Epstein–Barr virus infection with cutaneous and sinus lymphoproliferation in a white female patient with 25 years' follow‐up: an original case report. (8th September 2015) - Picard, C.; Gouarin, S.; Comoz, F.; Barreau, M.; Verneuil, L.; Troussard, X.; Dompmartin, A.
Summary: Chronic active Epstein–Barr virus infection (CAEBV) is characterized by chronic infectious mononucleosis‐like symptoms associated with very high viral load, as assessed by quantitative polymerase chain reaction. We present an unusual case in a French woman who was followed up over 25 years with cutaneous and sinus lymphoproliferation. This white woman presented with a long history of recurrent cutaneous necrotic papules of the skin, which started during childhood and healed spontaneously with depressed scars. The lesions spread to the left maxillary sinus and were associated with hepatomegaly and splenomegaly with no other visceral locations. Pathological examination of the skin and sinus revealed a dermal monoclonal T‐cell lymphoproliferative disorder, CD7 + and CD20 −, with no epidermotropism. T‐cell receptor rearrangement was positive, showing the monoclonality from the first biopsy. This T‐cell proliferation was positive for EBV‐encoded small RNA and was associated with a high EBV viral load. Since then, the patient has been in good health, despite a permanently high EBV viral load. Hydroa vacciniforme (HV)‐like lymphoma and natural killer/T‐cell lymphoma were discussed, but none really fit our case. Natural killer cell lymphoma was ruled out because of the indolent course, but sinus lesions do not exist in HV‐like lymphoma. A therapeutic approach is difficult because of the coexistence of viral infection and monoclonal T‐cell proliferation. Chemotherapy is not efficient and induces immunosuppression, which may worsen the prognosis. Although rituximab may have an immunomodulatory function, it was not effective in our case. Abstract : What's already known about this topic? Chronic active Epstein–Barr virus infection (CAEBV) is characterized by chronic infectious mononucleosis‐like symptoms associated with very high viral load. A therapeutic approach is difficult because of the coexistence of viral infection and monoclonal T‐cell proliferation. Immunomodulation is probably the best alternative treatment for these patients. What does this study add? We present an unusual case of CAEBV, classified as A2 according to Ohshima et al ., in a French woman who was followed up over 25 years with cutaneous and sinus lymphoproliferation.